Implementasi Pendidikan Karakter Perspektif Islam - Rosidah Rosidah; Muhammad Syahrindra Sofyan Pangestu (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2023)
ABSTRACT. This research is motivated by the rise of cases involving students such as brawls between students, sexual harassment, drinking, narcotics and so on, this indicates that there is a lack and weakness of moral and character education. This study aims to describe character education from an Islamic perspective, to describe the management of character education from a general perspective, to know the management of character education from an Islamic perspective. The research method used is library research, looking for relevant sources according to the topic of discussion such as books, articles, journals and other documentation. The analysis technique consists of grouping the literature, briefly elaborating the results of the grouping, and analyzing the content of the relevant literature so that it becomes a scientific paragraph. The results of this study are 1) Islamic perspective character education is the distribution of knowledge based on noble character from the time of growth to the end of life with various educational models that aim to form civilized and moral behavior to humans so that they are obedient and obedient to Islamic teachings which then give strength and benefits for the nation and state as a form of acknowledgment of the existence of God. 2) Management of character education according to the general view, namely the management of the education system both nationally, regionally, and units (schools) through the implementation of management functions to suit the character of the nation and religion as an effort to shape the character of students with noble character by utilizing elements of character education. -elements of efficient management. 3) Management of Islamic perspective character education is to implement Islamic perspective character education effectively and efficiently as well as comprehensively and intact with proper management in educational institutions. Starting from implementing management functions and all elements of management.